MASS INCARCHMENT: : REFLECTIONS BEFORE THE HEALTH CRISIS BY THE NEW CORONAVIRUS - Bezerra da Silva, José Júnior (Revista Gênero e Interdisciplinaridade, 2021)
Data from the National Prison Information Survey show that Brazil is the third country in the world in numbers of people deprived of their liberty. These data lead us to think that if the historical denunciations of race-based inequalities made by black movements are not enough, it is necessary to foster a rapprochement with historical and current academic and intellectual productions, of black and black thinkers, and committed non-blacks with the theme. This study is a review of the work Encarceramento em Massa by Juliana Borges. In view of the emergence of this social practice, we relate the problem of mass incarceration in Brazil (and the way it affects the country’s black population) with the current health crisis caused by the new Coronavirus (COVID-19). In general lines, from this context, a Necropolitical logic is reinforced, arising from the colonialist logic of putting the lives of some groups in constant contact with death, of making people live and letting them die